Given that a n = n 2 ( cos 2 3 n π − sin 2 3 n π ) ( n ∈ N + ) , let S n = k = 1 ∑ n a k .
b n = n ⋅ 4 n S 3 n ( n ∈ N + ) , T n = k = 1 ∑ n b k .
T 1 0 = q p , where p , q are positive coprime integers.
Submit ⌊ p − q + 2 ( S 1 0 0 + S 2 0 1 + S 3 0 2 ) ⌋ .
Have a look at my problem set: SAT 1000 problems
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
S 3 n = 2 n ( 9 n + 4 ) ⟹ S 2 0 1 = 2 4 0 6 6 9
S 3 n + 1 = − 2 2 n + 1 ⟹ S 1 0 0 = − 2 6 7
S 3 n + 2 = − 2 9 n 2 + 1 4 n + 5 ⟹ S 3 0 2 = − 2 9 1 4 0 5
b n = 2 2 n + 1 9 n + 4 ⟹
T n = 3 × 2 2 n − 3 2 2 n − 1 − 2 2 n + 1 3 n
⟹ T 1 0 = 1 0 4 8 5 7 6 2 7 9 6 1 8 5
Hence the required answer is 1 6 9 6 8 0 6 .
Problem Loading...
Note Loading...
Set Loading...
Given that a n = n 2 ( cos 2 3 n π − sin 2 3 n π ) = n 2 cos 3 2 n π = ⎩ ⎨ ⎧ − 2 n 2 n 2 if n m o d 3 = 0 if n m o d 3 = 0
Now consider
S 3 n = − 2 1 2 − 2 2 2 + 3 2 − 2 4 2 − 2 5 2 + 6 2 − ⋯ − 2 ( 3 n − 2 ) 2 − 2 ( 3 n − 1 ) 2 + ( 3 n ) 2 = 2 3 k = 1 ∑ n ( 3 k ) 2 − 2 1 k = 1 ∑ 3 n k 2 = 2 2 7 k = 1 ∑ n k 2 − 2 1 k = 1 ∑ 3 n k 2 = 2 2 7 ⋅ 6 n ( n + 1 ) ( 2 n + 1 ) − 2 1 ⋅ 6 3 n ( 3 n + 1 ) ( 6 n + 1 ) = 4 n ( 9 ( 2 n 2 + 3 n + 1 ) − ( 1 8 n 2 + 9 n + 1 ) = 2 n ( 9 n + 4 )
Then we have:
⟹ S 3 n + 1 ⟹ S 3 n − 1 S 1 0 0 S 2 0 1 S 3 0 2 = 2 n ( 9 n + 4 ) − 2 ( 3 n + 1 ) 2 = 2 n ( 9 n + 4 ) − ( 3 n ) 2 = S 3 ⋅ 3 3 + 1 = 2 3 3 ( 9 ⋅ 3 3 + 4 ) − 2 1 0 0 2 = − 3 3 . 5 = S 3 ⋅ 6 7 = 2 6 7 ( 9 ⋅ 6 7 + 4 ) = 2 0 3 3 4 . 5 = S 3 ⋅ 1 0 1 − 1 = 2 1 0 1 ( 9 ⋅ 1 0 1 + 4 ) − 3 0 3 2 = − 4 5 7 0 2 . 5
And:
⟹ b n ⟹ T n ⟹ T 1 0 = 4 n n S 3 n = 2 ⋅ 4 n 9 n + 4 = k = 1 ∑ n b k = k = 1 ∑ n 2 ⋅ 4 k 9 k + 4 = 8 9 k = 1 ∑ n 4 k − 1 k + 2 1 k = 0 ∑ n − 1 4 k 1 = 8 9 k = 1 ∑ n d x d x k ∣ ∣ ∣ ∣ x = 4 1 + 2 1 ( 1 − 4 1 1 − 4 n 1 ) = 8 9 ⋅ d x d k = 1 ∑ n x k ∣ ∣ ∣ ∣ x = 4 1 + 2 1 ( 4 n − 4 n − 1 4 n − 1 ) = 8 9 ⋅ d x d [ 1 − x x ( 1 − x n ) ] x = 4 1 + 6 ⋅ 4 n − 1 4 n − 1 = 8 9 [ ( 1 − x ) 2 n x n + 1 − ( n + 1 ) x n + 1 ] x = 4 1 + 6 ⋅ 4 n − 1 4 n − 1 = 2 ( 4 n + 1 4 n + 1 − 3 n − 4 ) + 6 ⋅ 4 n − 1 4 n − 1 = 6 ⋅ 4 n 1 6 ( 4 n − 1 ) − 9 n = 6 2 9 1 4 5 6 1 6 7 7 7 1 1 0 = 1 0 4 8 5 7 6 2 7 9 6 1 8 5
Therefore ⌊ p − q + 2 ( S 1 0 0 + S 2 0 1 + S 3 0 2 ⌋ = 1 6 9 6 8 0 6 .